Iterative synthesis of nitrogen-containing polyketide via oxime intermediates. Issue 9 (11th February 2022) - Takeuchi, Yuta; Kawasaki, Shun; Akagawa, Kengo; Kudo, Kazuaki
Abstract : An iterative synthesis of nitrogen-containing polyketides has been developed. Structurally diverse polyketides with nitrogen functional groups were obtained by the uniform protocol. Abstract : Typical polyketides consist of C, H, and O atoms, whereas several types of N-containing polyketides are known to show intriguing properties. Because conventional synthetic approaches for such compounds focus on only specific structures, a more general method is desirable. Here, we have developed an iterative synthesis of nitrogen-containing polyketide. Chain elongation of carboxylic acid via decarboxylative Claisen condensation with malonic acid half thioester was iteratively performed to construct carbon frameworks. β-Keto groups formed by the chain elongation were appropriately converted to O -methyl oximes for incorporation of nitrogen atoms. Cyclization of the resulting oxime intermediates followed by reductive N–O cleavage afforded structurally diverse nitrogen-containing polyketides such as 2-pyridone, 4-aminopyrone, and 4-aminosalicylate. This method was finally applied to the synthesis of ( R )-6-aminomellein, which is a nitrogen-substituted derivative of bioactive compound, ( R )-6-methoxymellein. The versatility of the present method would enable the synthesis of diverse polyketides with nitrogen functional groups, which can be potentially utilized for the development of novel bioactive compounds.